Inovasi biofon sebagai upaya pemanfaatan limbah lindi tempat pembuangan akhir (TPA) dan molase menjadi rehabilitator tanah - Humairo, Mika Vernicia; Nizar, Qonita Qotrunnada; Novitasari, Zahra Rizki; Safira, Revina (Holistik Jurnal Kesehatan, 2025)
Background: The problem of organic waste in landfills, particularly in Malang City, remains a serious challenge in maintaining environmental quality and public health. The volume of waste in Malang City reaches 778.38 tons per day, and it remains unprocessed. The decomposing organic waste produces leachate, which contains hazardous pollutants but also has the potential to be a source of nutrients. Purpose: To develop biophones as an effort to utilize landfill leachate and molasses as a soil rehabilitator. Method: A laboratory experiment was conducted by mixing leachate, molasses, and EM4, which were fermented for 21 days. The resulting fermentation was then tested for nutrient content in the laboratory. Results: The organic carbon (0.89%), nitrogen (0.02%), potassium (0.10%), and pH (5.1) content did not meet the minimum standards for liquid organic fertilizer (POC), but they had considerable potential as soil amendments. The content of microelements, such as manganese (24 ppm), showed a contribution to soil quality. Conclusion: Biofon has the potential to improve soil chemical properties, particularly pH. Further development is recommended, including the addition of carbon-, nitrogen-, and phosphorus-rich materials, as well as application testing on various soil types to ensure its effectiveness and safety.   Keywords: Biofon; Final Disposal Site; Leachate; Molasses; Soil Rehabilitation.   Pendahuluan: Permasalahan sampah organik di Tempat Pembuangan Sampah (TPS), khususnya di Kota Malang masih menjadi tantangan serius dalam menjaga kualitas lingkungan dan kesehatan masyarakat. Jumlah sampah di Kota Malang mencapai 778.38 ton per hari dan tidak terolah setiap harinya. Sampah organik yang membusuk menghasilkan cairan lindi (leachate) yang mengandung bahan pencemar berbahaya, namun juga memiliki potensi sebagai sumber unsur hara.  Tujuan: Untuk mengembangkan biofon sebagai upaya pemanfaatan limbah lindi tempat pembuangan akhir (TPA) dan molase menjadi rehabilitator tanah. Metode: Penelitian eksperimen laboratorium dengan mencampurkan lindi, molase, dan EM4, difermentasi selama 21 hari. Hasil fermentasi kemudian diuji kandungan unsur haranya di laboratorium.  Hasil: Kandungan C-organik (0.89%), nitrogen (0.02%), kalium (0.10%), dan pH (5.1) belum memenuhi standar minimal pupuk organik cair (POC), namun cukup potensial sebagai pembenah tanah. Kandungan unsur mikro seperti mangan (24 ppm) menunjukkan kontribusi terhadap kualitas tanah. Simpulan: Biofon berpotensi memperbaiki sifat kimia tanah, khususnya pH. Pengembangan lanjutan disarankan dengan penambahan bahan kaya karbon, nitrogen, dan fosfor, serta uji aplikatif pada berbagai jenis tanah untuk memastikan efektivitas dan keamanannya.   Kata Kunci: Biofon; Limbah Lindi; Molase; Rehabilitator Tanah; Tempat Pembuangan Akhir (TPA).